Michael “Mike” Llewellyn Hadley: 6 April 1936–4 March 2026 - Yeates, Ian; Glover, William; Sarty, Roger; Gimblett, Richard; Drent, Jan (The Northern Mariner / Le marin du nord, 2025)
Michael Hadley, professor emeritus, University of Victoria, and captain (retired) in the naval reserves, lived life as a great adventure with passion, compassion, and outstanding achievements in his many endeavours. Maritime history was only one of those endeavours, which included command responsibilities in the navy, literature and language studies and teaching, and service to social justice causes. We were fortunate that he was active in the Canadian Nautical Research Society from its beginnings until not long before his passing. Below are memories and reflections that members of the society shared in response to the news of Michael’s passing. The lead item is a biographical note that Ian Yeates was inspired to draw from Michael’s distinguished memoir, Boxing the Compass, that appeared in 2024 and won a Keith Matthews Award, the sixth Keith Matthews Award Michael received for his maritime publications.